The Role of Tranexamic Acid in Managing Traumatic Hemorrhage: A Review of Current Evidence - Makulec, Aleksandra; Szredzka, Aleksandra; Otrębska, Katarzyna; Lewandowska, Dominika; Jóźwik-Szymańska, Aleksandra; Kostecka, Natalia; Mikuła, Laura; Bogdan-Groszyk, Zuzanna; Kucharski, Jan; Muszyńska, Helena (Quality in Sport, 2026)
Introduction. Traumatic hemorrhage is one of the leading causes of death among patients with severe injuries. Tranexamic acid (TXA), a synthetic antifibrinolytic agent, has shown potential to reduce massive blood loss and decrease mortality. Aim. The aim of this study was to analyze current evidence regarding the efficacy and safety of tranexamic acid in the treatment of traumatic hemorrhage and to assess the factors influencing its therapeutic effect. Methods. A literature review was conducted covering publications (2010-2026), including clinical studies, randomized controlled trials, systematic reviews, and meta-analyses concerning the use of TXA in trauma patients. Data on the timing and route of administration, dosing, efficacy, and safety of therapy were analyzed. Results. TXA reduces blood loss and may lower mortality, especially when administered early after injury. Intravenous use is standard, while intraosseous or intramuscular routes may be used prehospital. TXA is generally safe, but monitoring for thromboembolic events and dose-related adverse effects is recommended in patients with multiple injuries. Conclusions. TXA is an effective and safe option in traumatic hemorrhage management. Its efficacy depends on timing, dosing, and patient factors. Early use improves outcomes, but further research is needed to optimize treatment and assess alternative administration routes.